The Role of UPT Library in Digital Literacy at Tadulako University - Amil Amrillah; Achmad Herman; Sitti Murni Kaddi (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
The aims of this research are: 1) to find out the role of UPT Libraries in digital literacy at Tadulako University. 2) To find out the obstacles to implementing digital literacy at UPT. Tadulako University Library. The type of research used is action research with data analysis techniques, namely by doing data reduction, data presentation, and data validation and drawing conclusions. In the discussion there are 3 UPT roles. Untad Library in digital literacy, namely: 1) As a digital literacy media, 2) as a digital information manager, 3) as a bearer of digital literacy culture. The results of the study explain that the role of the UPT. The Untad Library as an information medium through the proQuest electronic journal, Android-based E-Books, Pocadi services (Digital Reading Corner) and provision of internet service rooms. The role of information management consists of; Processing of the SLIMS database, repository, and Tadulako University e-library. In the role of carrier of literacy culture, UPT Library Untad conducts socialization of digital services, carries out webinars, library exhibition activities. From the results of this role research it has been implemented and found obstacles to role optimization, namely the quality of human resources, budgetary resources, and the lack of policies on digital literacy services. and there are also external constraints, namely the lack of effective librarian communication with users, lack of collaboration between university libraries, ineffective internet network, and also user interest in reading are constraining factors in maximizing the role of the UPT Library in digital literacy at Tadulako University.